2021
DOI: 10.1097/tin.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Levels and the Risk of Pneumonia in Children

Abstract: This systematic review and meta-analysis aimed to evaluate the association between serum vitamin D concentrations and the risk of pneumonia in children. Human studies reporting serum vitamin D levels in children with pneumonia and healthy controls were collected from different databases. The standardized mean difference and 95% confidence interval were calculated to evaluate the relationship between risk incidence of pneumonia and serum vitamin D levels. The results of analysis showed that serum vitamin D leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…The odds ratio (OR) of study participants suffering from severe pneumonia with severe Vitamin D deficiency was estimated at 3.72 on the CURB-65 scoring pattern. Our findings of the study are consistent with a Similar study done among the general population in Germany by Tang et al, which revealed the existence of a positive correlation between serum Vitamin D levels and prevalence as well as the severity of community-acquired pneumonia on the CURB 65 score [20].…”
Section: Discussionsupporting
confidence: 93%
“…The odds ratio (OR) of study participants suffering from severe pneumonia with severe Vitamin D deficiency was estimated at 3.72 on the CURB-65 scoring pattern. Our findings of the study are consistent with a Similar study done among the general population in Germany by Tang et al, which revealed the existence of a positive correlation between serum Vitamin D levels and prevalence as well as the severity of community-acquired pneumonia on the CURB 65 score [20].…”
Section: Discussionsupporting
confidence: 93%